Opposing modulation of Cx26 gap junctions and hemichannels by CO2. (22nd October 2020) - Nijjar, Sarbjit; Maddison, Daniel; Meigh, Louise; de Wolf, Elizabeth; Rodgers, Thomas; Cann, Martin J.; Dale, Nicholas
Abstract : Key points: A moderate increase in P C O 2 (55 mmHg) closes Cx26 gap junctions. This effect of CO2 is independent of changes in intra‐ or extracellular pH. The CO2 ‐dependent closing effect depends on the same residues (K125 and R104) that are required for the CO2 ‐dependent opening of Cx26 hemichannels. Pathological mutations of Cx26 abolish the CO2 ‐dependent closing of the gap junction. Elastic network modelling suggests that the effect of CO2 on Cx26 hemichannels and gap junctions is mediated through changes in the lowest entropy state of the protein. Abstract: Cx26 hemichannels open in response to moderate elevations of CO2 ( P C O 2 55 mmHg) via a carbamylation reaction that depends on residues K125 and R104. Here we investigate the action of CO2 on Cx26 gap junctions. Using a dye transfer assay, we found that an elevated P C O 2 of 55 mmHg greatly delayed the permeation of a fluorescent glucose analogue (NBDG) between HeLa cells coupled by Cx26 gap junctions. However, the mutations K125R or R104A abolished this effect of CO2 . Whole cell recordings demonstrated that elevated CO2 reduced the Cx26 gap junction conductance (median reduction 66.7%, 95% CI, 50.5–100.0%) but had no effect on Cx26 K125R or Cx31 gap junctions. CO2 can cause intracellular acidification. Using 30 mm propionate, we found that acidification in the absence of a change in P C O 2 caused a median reduction in the gap junction conductance of 41.7% (95% CI, 26.6–53.7%). This effect of propionate was unaffected by the K125R mutation (median reduction 48.1%, 95% CI, 28.0–86.3%). pH‐dependent and CO2 ‐dependent closure of the gap junction are thus mechanistically independent. Mutations of Cx26 associated with the keratitis ichthyosis deafness syndrome (N14K, A40V and A88V), in combination with the mutation M151L, also abolished the CO2 ‐dependent gap junction closure. Elastic network modelling suggests that the lowest entropy state when CO2 is bound is the closed configuration for the gap junction but the open state for the hemichannel. The opposing actions of CO2 on Cx26 gap junctions and hemichannels thus depend on the same residues and presumed carbamylation reaction. Key points: A moderate increase in P C O 2 (55 mmHg) closes Cx26 gap junctions. This effect of CO2 is independent of changes in intra‐ or extracellular pH. The CO2 ‐dependent closing effect depends on the same residues (K125 and R104) that are required for the CO2 ‐dependent opening of Cx26 hemichannels. Pathological mutations of Cx26 abolish the CO2 ‐dependent closing of the gap junction. Elastic network modelling suggests that the effect of CO2 on Cx26 hemichannels and gap junctions is mediated through changes in the lowest entropy state of the protein.